Recent progress in nanomaterials of battery energy storage: A patent landscape analysis, technology updates, and future prospects - Motalib Hossain M.A.; Ker P.J.; Tiong S.K.; Indra Mahlia T.M.; Hannan M.A. (Walter de Gruyter GmbH, 2025)
The world's energy demand has significantly increased as a result of the growing population and accompanying rise in energy usage. Fortunately, the innovation of nanomaterials (NMs) and their corresponding processing into devices and electrodes could enhance the functionality and/or advancement of the current battery energy storage systems (BESSs). Patent landscape analysis (PLA) can offer a comprehensive overview of technological development trends and enable discussion in interdisciplinary areas that facilitate more rational technology planning in the future. In this study, PLA of recent advancements in the NM-based BESS was critically analyzed, future technologies forecasted, and potential challenges outlined. A search was performed in the Lens database using "energy storage system,""battery,"and "nanomaterial,"and related patents under the simple family were extracted. Finally, after excluding duplicates and irrelevant patents, a total of 89 patents were selected for analysis using various parameters. The article provides a current technical overview along with an extensive bibliographic review of the patent family, trends of patent growth, key inventors and owners, patent legal status, patent jurisdiction, top cited patents, etc., as well as technological updates. Overall, nanotechnology has great potential for the future; however, further research and studies are necessary to accelerate the widespread usage of NMs in energy storage systems using cost-effective and environmentally friendly technologies. ? 2024 the author(s), published by De Gruyter.